Do internal controls improve integrity? A comparative study of central and regional governments - Nurmalasari, Devi; Dominicus Savio Priyarsono; Linda Karlina Sari (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Integrity is a cornerstone of good governance; yet, its realization remains uneven across various levels of government in Indonesia. This study aims to compare the influence of integrated internal control system components—risk management, internal audit, internal control systems, and corruption control—on the integrity of central and regional government agencies. A quantitative approach is employed using Spearman’s rank correlation and panel data regression analysis on data from 42 central and 491 regional agencies collected between 2022 and 2023. Model selection is based on the Chow, Hausman, and Breusch–Pagan tests. The results show that in regional agencies, risk management, internal control systems, and corruption control significantly enhance integrity, while internal audit does not. Conversely, none of the control components show a significant effect on integrity in central agencies, indicating a gap between system maturity and actual governance outcomes. These differences reflect contextual challenges, including bureaucratic complexity, limited leadership engagement, and a compliance-oriented implementation approach. The study concludes that tailored strategies are needed to strengthen internal audits in regional agencies and to move beyond procedural compliance in central institutions. The study offers practical implications for improving public governance and contributes novel insights through its comparative approach across government levels.